Karakteristik Petani Padi dan Struktur Biaya Usahatani Padi di Kecamatan Buahdua, Kabupaten Sumedang, Jawa Barat - Wiyono, Sulistyodewi Nur; Utami, Hesty Nurul; Puspitasari, Anisa; Salsabila, Dita Nur (Universitas Galuh, 2025)
This study aims to determine the characteristics of current rice farmers in Buahdua Sub-district, Sumedang Regency, how rice farming costs are structured, and how farmer characteristics are associated with land area and income. This research is a quantitative study with a survey research method that uses questionnaires for its research instruments. The population in this study was rice farmers in Buahdua Subdistrict, Sumedang Regency with a sample size used in this study of 65 respondents. The analytical tools used included descriptive statistics and cross tabulation. The results showed that the cost structure of rice farming in Buahdua District, Sumedang Regency consisted of the largest portion of fertilizer costs, followed by seed costs, pesticide costs and labour costs. In the results of cross tabulation analysis, it is known that male rice farmers tend to manage larger land and dominate the higher income group compared to women. The age group of 40-60 years dominates the highest income and most are classified as smallholders with land under 0.5 hectares.